Students' Mathematical Logical Thinking Skills through Kite Making in STEM Education - Risnanosanti Risnanosanti; Rotma Wati; Winda Ramadianti (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
This study investigates the enhancement of students' mathematical and logical thinking skills through kite-making activities using the STEM approach. Conducted with 28 ninth-grade students at SMP Negeri 03 Bengkulu Tengah, this qualitative descriptive research utilized observation, documentation, and interviews for data collection. Data were analyzed using the Miles and Huberman model, focusing on integrating geometry, measurement, and symmetry within the kite-making process. The findings reveal that STEM-based kite-making activities significantly improve students' logical reasoning and problem-solving skills by contextualizing abstract mathematical concepts into practical tasks. Students demonstrated the ability to sequence steps systematically, provide logical arguments, and draw accurate conclusions. These results emphasize the potential of project-based learning in fostering higher-order thinking skills. This study suggests that incorporating similar activities in the curriculum can enhance students' cognitive and practical competencies. Further research is recommended to explore its implementation across diverse educational levels and environments.